2020
DOI: 10.1177/1078155220959416
|View full text |Cite
|
Sign up to set email alerts
|

Initial tacrolimus weight-based dosing strategy in allogeneic hematopoietic stem-cell transplantation

Abstract: Tacrolimus is a mainstay medication for graft-versus-host disease (GVHD) prophylaxis in combination with other immunosuppressive agents. Achieving therapeutic tacrolimus levels is vital in preventing acute GVHD (aGVHD), while supratherapeutic levels may increase risk of toxicity and relapse. We performed a single center retrospective chart review including all adult patients post-allogeneic hematopoietic stem-cell transplantation who received initial tacrolimus continuous intravenous infusion for GVHD prophyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Thus, it is vital to prevent the risk of developing GVHD. Tacrolimus is currently the first-line drug used for the prevention of GVHD following HSCT and has played an important role in addressing this urgent clinical need ( Gao and Ma, 2019 ; Ishiwata et al, 2020 ; Soskind et al, 2020 ; Zhou et al, 2020 ). With the exception of potential rejection reactions, IFD has become a significant cause of morbidity and mortality in HSCT patients, and at present, posaconazole is often used as prophylactic therapy for prevention of IFD ( Zhang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is vital to prevent the risk of developing GVHD. Tacrolimus is currently the first-line drug used for the prevention of GVHD following HSCT and has played an important role in addressing this urgent clinical need ( Gao and Ma, 2019 ; Ishiwata et al, 2020 ; Soskind et al, 2020 ; Zhou et al, 2020 ). With the exception of potential rejection reactions, IFD has become a significant cause of morbidity and mortality in HSCT patients, and at present, posaconazole is often used as prophylactic therapy for prevention of IFD ( Zhang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HSCT significantly improves the quality of life of CD patients, and 50% of CD patients who underwent HSCT achieved complete healing of the mucosa and clinical remission ( Lindsay et al, 2017 ; Lopez-Garcia et al, 2017 ; Ruiz et al, 2020 ). However, for HSCT patients, long-term tacrolimus treatment is necessary to prevent rejection ( Gao and Ma, 2019 ; Ishiwata et al, 2020 ; Soskind et al, 2020 ; Zhou et al, 2020 ). Similarly, posaconazole is also needed for the prevention of invasive fungal disease (IFD) in HSCT patients ( Busca et al, 2016 ; Zhang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tacrolimus is a first-line agent for GVHD prevention and has been routinely employed to stop rejection of HSCT [15][16][17][18]. However, tacrolimus has a narrow therapeutic range; the use of high concentrations seems to be related to toxicity, while lower concentrations are related to an acute rejection's increased risk (23).…”
Section: Discussionmentioning
confidence: 99%
“…HSCT may adjust superoxide generation, making neutrophil function within normal range and improvement in inflammatory progression (14). However, HSCT patients must take tacrolimus, a potent immunosuppressant, for a prolonged period to prevent transplant rejection (15)(16)(17)(18). In addition, voriconazole, a second-generation triazole with potent broad-spectrum antifungal activity, is used for prophylaxis against invasive fungal disease (IFD), which is a major cause of morbidity and mortality in pediatric patients after HSCT (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…For HSCT patients, tacrolimus, an immunosuppressant, needs to be taken for a long time to prevent rejection (Gao and Ma, 2019;Ishiwata et al, 2020;Soskind et al, 2020). However, tacrolimus had high pharmacokinetic variability, making it difficult to formulate an individual administration schedule, especially in children with SCID undergoing HSCT.…”
Section: Introductionmentioning
confidence: 99%